(untitled) (Medical Forum Monthly, 2024)
Objective: To observe the different presentation and reproductive performance of women with congenital anomalies detected by ultrasound, hysterosalpingography and on laparotomy. Study Design: Prospective observational study. Place and Duration of Study: This study was conducted in the Department of Obstetrics & Gynaecology at Peoples Medical College Hospital Nawabshah from January 2004 to December 2009. Materials and Methods: All the women with congenital anomalies of genital tract detected clinically, by ultrasound and hysterosalpingography, attended the outpatient department or presented with a complication and operated; and or those who were incidentally diagnosed during cesarean section or on laparotomy were included in this study. Results: 48 patients with different mullerian duct anomalies were detected during the study period. Their age varied from 15 to 40 years. Mullerian agenesis with absent vagina was found in 6 cases, transverse vaginal septum was found in an other 6 patients. These patients presented with primary amenorrhoea, haematometra and haematocolpos. Imperforated hymen was found in 10 patients. They also present with a primary amenorrhoea, mass in lower abdomen and cyclical pain, few patients presented with acute retention of urine. Longitudinal vaginal septum was found in 3 cases. They presented with dyspareunia and difficult labour. Bicornuate uterus was found in 9 cases. They presented with malpresentations, recurrent abortion and preterm labour. Unicornuate uterus was found in 3 cases. Who were presented with ectopic pregnancy. Uterus didelphys was found in 3 cases, 5 patients had arcuate uterus, 3 patients presented with congenital second degree uterovaginal prolapse. Conclusion: Uterine abnormalities are not uncommon, although not all the types of uterine anomalies can affect the fertility but most of the time they have bad impact on fertility. Early diagnosis and treatment of these conditions may improve the fertility prospectus and also prevents various obstetrical complications.